Skills to use digital resources - Vazufa, Khudiyeva (Technium Social Sciences Journal, 2022)
As we know, it is possible to have a more practical and productive result if skills and habits are formed and developed in various applications of knowledge. In this process, the dialectic unity of knowledge, skills and habits acts as an important factor in ensuring optimality and determining development. Skills are more related to job position, workplace. One is irrelevant without the other. Taking into account the high dynamics of the development of digital activity, we can say that these skills are of vital importance. The interdisciplinary nature of skills, that is, the content or semantic load of skills, can span several different subject areas. The need for constant updating of digital skills is a result of the rapid development of technological equipment and information systems. As a rule, competitiveness factors of mobility and skills to be combined in virtual space to solve common problems across administrative and international borders exist and are developing with an increasing trend. The role of international standards, in which a comprehensive system is formed by the world community, which provides products and processes with "openness" features, is growing and forms the unique laws of information technology.